Teaching Model Driven Language Handling - Gjøsæter, Terje; Prinz, Andreas (Electronic Communications of the EASST, 2011)
Many universities teach computer language handling by mainly focussing on compiler theory, although MDD (model-driven development) and meta-modelling are increasingly important in the software industry as well as in computer science. In this article, we share some experiences from teaching a course in computer language handling where the focus is on MDD principles. We discuss the choice of tools and technologies used in demonstrations and exercises, and also give a brief glimpse of a prototype for a simple meta-model-based language handling tool that is currently being designed and considered for future use in teaching.